种考虑大规模电动汽车接入的电网双层优化调度方法 (2018)
本发明属于电力系统运行和调度领域，涉及种考虑大规模电动汽车接入的电网双层优化调度方法。本发明从输电网和配电网两个层次研究电动汽车的充放电策略，从输电网得出电动汽车最优充电时间，进而指导配电网中电动汽车最优充电位置，而配电网络的负荷如图1所示都集中在输电网上的某节点上。本发明还综合考虑了风电、基荷和火力发电机组以及电动汽车充放电的协调作用，并且用该模型对电动汽车充放电的时间和位置提出了有效的建议。 The invention belongs to the field of electric power system operation and dispatch and relates to a power-grid double-layer optimized dispatching method considering large-scale electric automobile access. Charging and discharging strategies of electric automobiles are researched from two aspects of a power transmission network and a power distribution network, the optimal charging time of the electric automobiles is determined through the power transmission network, further the optimal charging positions of the electric automobiles in the power distribution network are guided, and the load of the power distribution network is centralized on a certain node of the power transmission network, as shown in figure 1. In the power-grid double-layer optimized dispatching method, the coordination effect of wind power, bas